Technological Methods and Security of Information Resources in Dame Patience Goodluck Jonathan Automated Library, Ignatius Ajuru University of Education - Opara, Onyinyechi; Nsirim, Onyema; Irokah, Princess Lilian (Southern African Journal of Security)
This study investigates technological methods and security of information resources at Dame Patience Goodluck Jonathan Automated Library, Ignatius Ajuru University of Education. The study adopted a descriptive research survey design. The population of the study was 32 library staff comprising professionals and para-professionals in Dame Patience Goodluck Jonathan Automated Library, Ignatius Ajuru University of Education. A census sampling technique was used to select the entire population. The questionnaire was used for data collection and 27 copies of the questionnaires were found valid for data analysis. The study was analysed using simple percentages and mean and standard deviation were applied. The study revealed that the information resources available in Dame Patience Goodluck Jonathan Automated Library comprise of books, e-books, journals, e-journals, databases, encyclopaedias, the bible, and fiction. The security threats to information resources were mutilation, theft, microbes, humidity, and unauthorised access. The technological methods adopted to secure library resources were computers and burglary protection. Several challenges were found to militate against the security of information resources in the library such as lack of funds to procure security equipment, poor adoption of technological methods, lack of state-of-the-art infrastructure, and nonchalant attitudes of staff towards security measures to protect information resources. The study recommended the adoption of technologies such as CCTV, biometrics, and electronic doors in the security of library resources and training staff on their usage.